Politik Islam di Zaman Pra-Kemerdekaan - Sharfina Permata Noor, Erla; Hasan, Ahmadi; Umar, Masyithah; Khasyi'in, Nuril (PT. Sharia Journal and Education Center, 2024)
Abstract This research examines the politics of Islam during the pre-independence period in Indonesia and its role in the nation's struggle. Islamic politics during that period had a significant impact on Indonesia's history of struggle. Prior to the independence in 1945, Indonesia experienced more than three centuries of colonization by the Netherlands. Islamic politics became a major force in organizing society and fighting for independence. Islamic political movements emerged as a response to the colonization and modernization efforts carried out by the Dutch colonial government. Islamic politics during the pre-independence period in Indonesia were grounded in a strong religious spirit. Islam played a central role in the lives of Indonesian society, and Islamic figures at that time viewed politics as a means to advocate for justice, freedom, and the welfare of the Muslim community. Islamic politics were also influenced by global political shifts at that time. Islamic organizations such as Sarekat Islam, Muhammadiyah, and Nahdlatul Ulama played a crucial role in coordinating the political, social, and cultural struggles of the Muslim community in Indonesia. Islamic political parties such as the Masyumi Party also played a significant role in shaping Islamic political perspectives and influencing the national political direction of Indonesia. Additionally, it showcases the role of Islamic politics in the national awakening movement towards achieving independence. Keywords : Politics of Islam, Pre-independence Era, Islamic Organizazion Abstrak Penelitian ini membahas politik Islam pada masa pra-kemerdekaan Indonesia dan perannya dalam perjuangan bangsa. Politik Islam pada periode tersebut memiliki dampak yang signifikan dalam sejarah perjuangan Indonesia. Sebelum kemerdekaan pada tahun 1945, Indonesia mengalami penjajahan oleh Belanda selama lebih dari tiga abad. Politik Islam menjadi kekuatan utama dalam mengorganisir masyarakat dan memperjuangkan kemerdekaan. Gerakan politik Islam mulai muncul sebagai respons terhadap penjajahan dan modernisasi yang dilakukan oleh pemerintah kolonial Belanda. Politik Islam pada masa pra-kemerdekaan Indonesia didasarkan pada semangat agama yang kuat. Agama Islam memainkan peran sentral dalam kehidupan masyarakat Indonesia, dan tokoh-tokoh Islam pada masa itu melihat politik sebagai sarana untuk memperjuangkan keadilan, kebebasan, dan kesejahteraan umat. Politik Islam juga dipengaruhi oleh pergeseran politik global pada saat itu. Organisasi Islam seperti Sarekat Islam, Muhammadiyah, dan Nahdlatul Ulama menjadi kekuatan penting dalam mengoordinasikan perjuangan politik, sosial, dan budaya umat Islam di Indonesia. Partai politik Islam seperti Partai Masyumi juga memainkan peran penting dalam merumuskan pandangan politik Islam dan mempengaruhi arah politik nasional Indonesia. Selain itu juga memperlihatkan peran politik Islam dalam moment kebangkitan nasional untuk mencapai kemerdekaan. Kata Kunci : Politik Islam, Pra-Kemerdekaan, Organisasi Islam